Human CLA+ Memory T Cell and Cytokines in Psoriasis - de Jesús-Gil, Carmen; Sans-de San Nicolàs, Lídia; García-Jiménez, Irene; Ferran, Marta; Pujol, Ramon M.; Santamaria-Babí, Luis F. (Frontiers in Medicine, 2021)
Psoriasis is a common inflammatory skin condition resulting from the interplay between epidermal keratinocytes and immunological cellular components. This sustained inflammation is essentially driven by pro-inflammatory cytokines with the IL-23/IL-17 axis playing a critical central role, as proved by the clinical efficacy of their blockade in patients. Among all the CD45R0+ memory T cell subsets, those with special tropism for cutaneous tissues are identified by the expression of the Cutaneous Lymphocyte-associated Antigen (CLA) carbohydrate on their surface, that is induced during T cell maturation particularly in the skin-draining lymph nodes. Because of their ability to recirculate between the skin and blood, circulating CLA+ memory T cells reflect the immune abnormalities found in different human cutaneous conditions, such as psoriasis. Based on this premise, studying the effect of different environmental microbial triggers and psoriatic lesional cytokines on CLA+ memory T cells, in the presence of autologous epidermal cells from patients, revealed important IL-17 cytokines responses that are likely to enhance the pro-inflammatory loop underlying the development of psoriatic lesions. The goal of this mini-review is to present latest data regarding cytokines implicated in plaque and guttate psoriasis immunopathogenesis from the prism of CLA+ memory T cells, that are specifically related to the cutaneous immune system.